Analisis Quality of Service (QoS) Jaringan Internet Universitas Menggunakan Metode Hierarchical Token Bucket (HTB) - Valia Yoga Pudya Ardhana; Mulyodiputro, M. Dermawan (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Qamarul Huda Badaruddin University is a private university located in Central Lombok Regency with an increasing number of students. Along with the increasing number of students, of course, the number of internet users on campus also increases, making traffic on the network more complex and requiring network management. Quality of Service (QoS) can be regarded as a terminology used to define the characteristics of a network service (Service) to find out how good the quality is in that service. With Quality of Service (QoS), bandwidth can be used optimally so as to improve the quality of internet services received by users. The application of appropriate bandwidth management needs to be done, one of which is using the HTB method, namely bandwidth management with bandwidth borrowing queuing techniques between classes or users. Which can allocate bandwidth according to the user's bandwidth requirements in accordance with the specified priority. The purpose of this study is to determine the Quality of Service (QoS) produced by the HTB method in conducting bandwidth management so as to improve existing internet services at Qamarul Huda Badaruddin University. The results of the Quality of Service (QoS) analysis based on the tests that have been carried out show that by applying the Hierarchical Token Bucket (HTB) method, satisfactory results are obtained, namely a value of 3.67. These results are obtained from the average test results on 4 parameters, namely delay, jitter, packet loss, and throughput.